Cultivating critical consciousness through a Global Health Book Club - Collins, Sarah L.; Case, Stuart J.; Rodriguez, Alexandra K.; Allen, Acquel C.; Wood, Elizabeth A. (Frontiers in Education, 2023)
Introduction Central to public health practice is mindfulness and intentionality toward achieving social justice and health equity. However, there is limited literature published on how educators are integrating these concepts into their curricular, pedagogical and instructional efforts. The goal of this study was to leverage the pluralistic views, social identities, and demographics within the classroom to explore the effects of introducing a Global Health Book Club (GHBC) assignment focused on identity of culture, equity, and power. We also sought to explore the use of first-account narratives illustrating the human experience as an instructional strategy to cultivate an empathic understanding of global health threats, while fostering critical consciousness toward one’s positionality within macro-level contexts. Finally, students were encouraged to reflect on their lived cultural experiences and engage in open and authentic dialogue with their peers. Methods We implemented a four-week GHBC assignment within an undergraduate global public health course. At the conclusion of the GHBC, students engaged in a reflective Individual Analysis Paper, which captured students’ perspectives on their cultural values and traditions, how these views shaped their understanding of their book, and evaluate whether their global perspective had changed as a result of the assignment. Thirty-one students consented to have their Individual Analysis Paper downloaded and de-identified for analysis. Student responses were analyzed using inductive thematic analysis procedures. Results Through our analysis, six themes, with several coinciding categories, were identified as salient. The themes include Demonstrated Empathy, Personal Reflection and Growth, Personally Inspired, Immersive Learning Experience, Broadened Perspective, and Provoked Emotion. Discussion Our findings support that a GHBC assignment is a viable and effective mechanism for engaging students in critical reflection, critical motivation and critical action. In cultivating a learning environment that promotes student-centered learning and active participation, students exemplified agency in their own learning. This work can serve as an exemplary model for other public health educators to engage students in reflective-based assignments regarding their positionality and critical consciousness. By utilizing frameworks conceived out of antiracism, diversity, equity, and inclusion, our work presents an innovative activity in engaging students in decolonization efforts within global public health practice.